Psychological outcomes and health-related quality of life changes in Chinese patients with moyamoya disease after revascularization - Liang, Haijuan; Yuan, Ping; Xu, Tong; Jin, Chao; Ji, Cuiling (Frontiers in Surgery, 2025)
ObjectivesThis study aimed to evaluate the psychological outcomes and changes in health-related quality of life (HRQOL) in Chinese patients with Moyamoya disease (MMD) following revascularization procedures.MethodsA total of 68 patients diagnosed with MMD and who underwent revascularization at Nanjing Drum Tower Hospital between January 2023 and January 2024 were retrospectively analyzed. Neuropsychological assessments, including the Trail Making Test, Chapuis Maze, Digit D2, Symptom Checklist-90 (SCL-90), Beck Depression Inventory-II (BDI-II), and the 36-item Short Form Health Survey (SF-36), were administered preoperatively and postoperatively at 3 months and 1 year. Statistical analysis was performed using SPSS version 29.0, with appropriate parametric or non-parametric tests applied based on data distribution.ResultsBaseline characteristics revealed no significant differences between the Unremarkable and Impaired groups, confirming comparability. Postoperative improvements were observed in HRQOL across multiple domains, particularly in patients with preoperative impairments. Significant improvements were seen in physical functioning, general health, physical pain, emotional role function, and vitality (P < 0.05). Psychological outcomes also showed significant improvements, with reductions in aggressiveness, anxiety, and somatization (P < 0.001). Depression scores significantly decreased in 29.4% of patients (P < 0.001), and executive function, as measured by TMTA, TMTB, and Digit D2, also showed significant improvements in the impaired group (P < 0.001). However, patients without preoperative impairments exhibited no significant changes in any of the assessed domains.ConclusionRevascularization significantly improves both psychological outcomes and HRQOL in Chinese patients with MMD, particularly in those with preoperative impairments. These findings highlight the importance of surgical intervention in enhancing both cognitive and psychological functioning in this patient population. Further prospective studies are warranted to confirm these results and explore long-term benefits.